PERTANGGUNGJAWABAN PERUSAHAAN MANAJER INVESTASI YANG TERLIBAT TINDAK PIDANA KORUPSI (STUDI KASUS PT. ASURANSI JIWASRAYA (PERSERO)) - Desovi, Rafiqa Aswinda; Kasyfi, Andio (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Corporate crime in Indonesia is a very difficult matter for law enforcers. In fact, this is very difficult, especially in terms of criminal liability and it is precisely this corporation that is deeply involved in business crimes, especially corruption. In 2018 and 2019 PT Asuransi Jiwasraya (Persero) announced that the company was in default to a number of its customers due to the wrong placement of investment funds which resulted in state losses. Several customers who felt that they were aggrieved have filed a lawsuit and criminal reports against PT Asuransi Jiwasraya (Persero). Meanwhile, the attorney general's office has also named several suspects suspected of being involved in criminal acts of corruption and causing PT Asuransi Jiwasraya (Persero), which in this case is a State-Owned Enterprise (BUMN) to suffered losses. This paper discusses about legal protection for victims of PT Asuransi Jiwasraya (Persero) and also discusses about the accountability of PT Asuransi Jiwasraya (Persero) as well as the role of state institutions to carry out company supervision of investment managers involved in the PT Asuransi Jiwasraya (Persero) case.